2001
DOI: 10.1046/j.0022-202x.2001.01388.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite Production, DNA Breakage, and Poly(ADP-ribose) Polymerase Activation in a Mouse Model of Oxazolone-Induced Contact Hypersensitivity

Abstract: Peroxynitrite-induced poly(ADP-ribose) polymerase activation has been implicated in the pathogenesis of various inflammatory conditions. Here we have investigated whether peroxynitrite and poly(ADP-ribose) polymerase may play a role in the pathophysiology of the elicitation phase of contact hypersensitivity. We have detected nitrotyrosine, DNA breakage, and poly(ADP-ribose) polymerase activation in the epidermis of mice in an oxazolone-induced contact hypersensitivity model. As tyrosine nitration is mostly med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 54 publications
5
56
1
Order By: Relevance
“…Inhibition of PARP-1 activity in airway epithelial cells, on the other hand, showed reduced NF-kB activation and reduced CXCL8 expression upon H 2 O 2 induction and prevented lung inflammation in vivo (Boulares et al, 2003). Similarly, CXCL8 as well as intercellular adhesion molecule-1 expression were reduced by PARP inhibitors in HaCaT keratinocytes (Szabo et al, 2001). These data indicate that PARP-1 can act as both an inhibitor and activator of NF-kB-dependent transcription.…”
Section: Discussionmentioning
confidence: 52%
“…Inhibition of PARP-1 activity in airway epithelial cells, on the other hand, showed reduced NF-kB activation and reduced CXCL8 expression upon H 2 O 2 induction and prevented lung inflammation in vivo (Boulares et al, 2003). Similarly, CXCL8 as well as intercellular adhesion molecule-1 expression were reduced by PARP inhibitors in HaCaT keratinocytes (Szabo et al, 2001). These data indicate that PARP-1 can act as both an inhibitor and activator of NF-kB-dependent transcription.…”
Section: Discussionmentioning
confidence: 52%
“…Several groups have reported that inhibition of PARP activity induces protection against necrotic cell death. However, PARP inhibition does not protect cells from apoptosis (Palomba et al, 1999;Szabó et al, 2001;Tentori et al, 2001). Thus, a role of PARP activation in necrosis is consistent with the fact that the inhibition or absence of PARP provides the most remarkable protection in disease models such as stroke, myocardial infarction, or mesenteric ischemia-reperfusion injury, which are characterized predominantly by necrotic-type cell death (Miesel et al, 1995).…”
Section: Parp and Cancer Chemotherapy 1009mentioning
confidence: 99%
“…For investigation of cellular viability, cells cultured in wells of 96-well microtiter plates were used and 10 μL MTT reagent (3-/4,5-dimethylthiazolyl-2/-2,5-diphenyltetrazolium bromide; 25 mg MTT/5 mL PBS) was pipetted into each well. Cells were incubated for 2 hours at 37°C and following addition of 100 μL of MTT solubilizing solution the absorption was detected at 570 nm using a Chameleon microplate reader (Hidex Ltd., Turku, Finland) on the second day of culturing [32].…”
Section: Measurement Of Cell Proliferation With 3 H-thymidine Labelinmentioning
confidence: 99%
“…Distal parts of the limb buds of Ross hybrid chicken embryos of Hamburger-Hamilton stages 22-24 were removed and primary micromass cultures of chondrifying mesenchymal cells were established from cell suspensions with a density of 15x10 6 cells/mL [17,32]. Droplets (100 mL) of the suspension were inoculated onto the bottom of plastic Petri dishes (Nunc, Naperville, IL, USA) with the day of inoculation is considered as day 0.…”
Section: Cell Culturingmentioning
confidence: 99%